Exercise-induced petechiae of the face in a teenager. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
In the child two paraphysiological petechial manifestations of the face are frequent: the first induced by various factors such as cough, vomiting that increase the pressure in the cephalic extremity specially in conjunction with febrile vasodilation and the second due to ex vacuo hemorrhages during the so-called game of the glass. Regarding the favoring role of physical exercise, the golfer’s purpura is well known: it occurs at the level of the legs of people over 50 (1) who play golf or who go on prolonged hikes during the hot period. This last form has also been described in children (2) who have intense physical activity in a warm environment always at the level of the legs in the area above the sock line. We have not found in the literature cases of petechiae of the face from intense physical exercise as in our teenager. In our case the history indicates a possible favoring factor of the hormonal stimulation.